Evaluation of the Campus Teaching Program Batch 6 on Literacy Improvement Based on the Kirkpatrick Model Level I and II at SMPN 1 MANIIS Grade VIII - Ala Aprila Ipungkarti; Dian Permata Sari (Eduvest - Journal of Universal Studies, 2024)
Program evaluation is one of the best ways to improve the quality of a program activity. The quality of the program will affect the achievement of goals for an institution or organization. The purpose of this research is to evaluate the effectiveness of the Campus Teaching Program Generation 6 in improving the literacy of eighth-grade students at SMPN 1 Maniis, based on Kirkpatrick Model Levels 1 and 2. The research method used is quantitative descriptive with a survey method, involving 30 eighth-grade students who participated in the Minimum Competency Assessment (AKM) Class. Data collection techniques were conducted using questionnaires, tests, observations, and documentation. The research results showed a significant improvement in students' literacy knowledge, with the average increasing from 31.83 to 56.83. Additionally, the acquisition of N-Gain Score (0.5792) and N-Gain Percent (58%) indicates that this program falls into the "Moderate" and "Sufficiently Effective" categories according to the Kirkpatrick Model. Overall, the Campus Teaching Program has proven to be effective in improving the literacy of eighth-grade students at SMPN 1 Maniis, in line with Kirkpatrick Model Levels 1 and 2. The implication suggests that this program is worthy of continuation.